Arterial stiffness and multiple organ damage: a longitudinal study in population - Scuteri, Angelo; Morrell, Cristopher H; Fegatelli, Danilo Alunni; Fiorillo, Edoardo; Delitala, Alessandro; Orru', Marco; Marongiu, Michele; Schlessinger, David; Cucca, Francesco (Aging clinical and experimental research, 2020)
Previous cross-sectional observation identified arterial aging, indexed as pulse-wave velocity (PWV), as a key determinant of the simultaneous multiple organ damage (heart, carotid artery, and kidney). The aim of the present cohort study is to investigate trajectories of repeated measures of PWV and traditional CV risk factors in subjects who eventually presented clinical evidence of multiple organ damage in the SardiNIA study. Organ damage was measured in the heart (left ventricular hypertrophy, LVH), the common carotid artery (intima-media thickness > 0.9 mm and/or plaque), and the kidney (eGFR < 60 ml/min/1.73 m ) of 2130 men and women of a broad age range participating the SardiNIA study. SHATS was defined as the simultaneous occurrence of all the three-organ damages. Trajectory in traditional CV risk factors and PWV was analyzed retrospectively (four observations over 9 years) according to the number of organ damage (from 0 to 3). Compared to subjects with no organ damage, after controlling for traditional CV risk factors, each 1 m/s increase in baseline PWV was accompanied by a 93% higher odds of developing SHATS; and each 1 cm/s (0.01 m/s) annual increase in PWV by a 31% greater odds of developing SHATS. Arterial stiffness, a proxy of arterial aging that can be measured clinically as PWV, is an integrated predictive marker of multiple age-associated organ damage recognized as clinical diseases.